Pluminasi as a New Composition Method in Contemporary Music | Pluminasi Sebagai Metode Komposisi Baru Pada Karya Musik Kontemporer - I Made Bayu Puser Bhumi; I Komang Sudirga; I Wayan Sudirana (Pusat Penerbitan LPPMPP ISI Denpasar, 2021)
The paradigm that was born from a mistake and misunderstanding of something different seemed to create a dividing barrier. Stigma has become a barrier between tradition and contemporary which is essentially related to one another. It takes a different perspective to find a correlation that will straighten out the